Integration of the Baltic States into the EU and institutios of fiscal convergence - Ali M. Kutan; Niina Pautola-Mol (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
This paper evaluates the functioning, suitability, and effectiveness of the Maastricht convergence criteria regarding fiscal policy and the Stability and Growth Pact for the Baltic States.We argue that the Maastricht fiscal targets from the Baltic perspective should be considered as long-term goals as opposed to short-run objectives of fiscal policy.Using the European Commission's approach as well as impulse response and variance decomposition techniques, we assess the fiscal discipline and cyclical sensitivity of each state's budget to changes in output gap.Empirical evidence indicates that Estonia and Latvia have been more successful in maintaining fiscal discipline than Lithuania during 1996-2000.We also observe that the Stability and Growth Pact signed in July 1997 would offer enough room for automatic fiscal stabilizers in Estonia and Latvia, but not necessarily in Lithuania.Policy implications of the findings for future perspectives are also discussed.
URN:NBN:fi:bof-201408072086
Keywords: 330; EU-enlargement; fiscal policy; Baltic countries